Використання сорбційних холодильних установок на об'єктах АПК в умовах надзвичайних ситуацій - Мартиненко, Олексій Геннадійович; Черепньов, Ігор Аркадійович; Вамболь, Сергій Олександрович (Державний біотехнологічний університет, 2024)
Considered the perspective of sorption refrigerating machines based on the en ergy of solar radiation for the storage of agricultural products. The possibility of use for medical purposes in emergency situations for the storage of vaccines and blood plasma was separately noted.
Keywords: холодильні установки; сорбційні холодильні установки; об'єкти АПК; надзвичайні ситуації; аграрний сектор; холодильні прилади